Disturbing Times Medieval Pasts, Reimagined Futures - Karkov, Catherine; Kłosowska, Anna; van Gerven Oei, Vincent W.J (Book collections on Project MUSE., 2020)
"From Kehinde Wiley to W.E.B. DuBois, from Nubia to Cuba, from Willie Doherty's terror in ancient landscapes to the violence of institutional Neo-Gothic, from Reagan's AIDS policies to Beowulf fanfiction, this richly illustrated volume brings together art historians and literature scholars to articulate a more inclusive, intersectional medieval studies. It will be of interest to students working on diaspora and migration, white settler colonialism and pogroms, Indigenous studies and decolonial methodology, slavery, genocide, and culturecide. The authors confront a legacy of medieval studies and its current failures, and analyze fascist, nationalist, colonialist, anti-Semitic, and other ideologies to which medieval was and is yoked. They set out concrete ethical choices and aims in research and teaching. In the face of rising global fascism and ideological mobilizations, contemporary and past, of cultural heritage and history as weapons of symbolic and physical oppression, the chapters on Byzantium, Medieval Nubia, Old English, Hebrew, Old French, Occitan, and American and European medievalisms brought together in this volume examine how educational institutions, museums, universities, and individuals are guided by ethics in research, collecting, and teaching. The volume includes pieces by current important voices in the field, including Andrea Myers Achi, Seeta Saganti, Vincent W.J. van Gerven Oei, Eva Frojmovic, Anna Kłosowska, Roland Betancourt, Joshua Davies, Alison Elizabeth Killilea, Catherine A.M. Clarke, Adam Miyashiro, Megan Cavell, Daniel Thomas, Stewart Brookes, Diane Watt, Jennifer Neville, Carla María Thomas, and Catherine Karkov"--